Pretreatment Platelet and Hemoglobin Levels Are Neither Predictive Nor Prognostic Variables for Patients With Locally Advanced Cervical Cancer Treated With Neoadjuvant Chemotherapy and Radical Hysterectomy: A Retrospective Italian Study. Issue 8 (1st October 2010) - Gadducci, Angiolo; Cosio, Stefania; Zola, Paolo; Tisi, Giancarlo; Ferrero, AnnaMaria; Piovano, Elisa; Cristofani, Renza; Greco, Carlo; Sartori, Enrico
Abstract : Background: To assess the predictive and prognostic values of pretreatment platelet and hemoglobin levels in patients with locally advanced cervical cancer who underwent neoadjuvant chemotherapy followed by radical hysterectomy. Methods: The authors retrospectively assessed 140 patients with FIGO (International Federation of Gynecology and Obstetrics) stage IB2-IIB cervical cancer who underwent chemosurgical treatment. Results: Median pretreatment platelet and hemoglobin levels were 272, 000/μL and 12.5 g/dL, respectively. Fourteen patients achieved a pathologically complete response, and 26 had an optimal partial response, with an optimal pathological response rate of 28.6%. By univariate analysis, optimal pathological response rate was associated with well/moderately differentiated grade ( P = 0.02) and platinum-/paclitaxel-based chemotherapy regimen ( P = 0.04), but not with platelet and hemoglobin levels. Multiple logistic regression confirmed that tumor grade (odds ratio, 2.827; 95% confidence interval [95% CI], 1.250-6.397; P = 0.01) and chemotherapy regimen (odds ratio, 5.416; 95% CI, 1.459-20.110; P = 0.01) were independent predictors of optimal pathological response. Five-year recurrence-free survival and 5-year overall survival were 66 % and 73%, respectively. By log-rank test, recurrence-free survival and overall survival were associated with pathological response ( P = 0.0002 and P = 0.001), lymph node status, ( P = 0.008 and P = 0.002), lymphovascular space status ( P = 0.005 and P = 0.003), and parametrial and/or surgical margin status ( P = 0.004 and P = 0.001), but not with platelet and hemoglobin levels. On multivariate analysis, pathological response (hazard ratio [HR], 7.999; 95% CI, 1.916-33.394; and HR, 6.007; 95% CI, 1.426-25.307) and parametrial and/or surgical margin status (HR, 2.061; 95%CI, 1.047-4.058; and HR, 2.561; 95% CI, 1.244-5.271) were independent prognostic variables of recurrence-free survival and overall survival. Conclusions: The achievement of an optimal pathological response is the strongest independent prognostic variable for patients with cervical cancer treated with neoadjuvant chemotherapy and radical hysterectomy, whereas pretreatment platelet and hemoglobin levels seem to be neither predictive of response to chemotherapy nor prognostic of long-term outcome.